2015
DOI: 10.1097/qai.0000000000000633
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Drug Use and HIV Drug Resistance Among HIV-Infected Black Men Who Have Sex With Men

Abstract: BACKGROUND HPTN 061 enrolled Black men who have sex with men in the United States. Some men with low/undetectable HIV RNA had unusual patterns of antiretroviral (ARV) drug use or had drugs detected in the absence of viral suppression. This report includes a comprehensive analysis of ARV drug use and drug resistance among men in HPTN 061 who were not virally suppressed. METHODS The analysis included 169 men who had viral loads >400 copies/mL at enrollment, including three with acute infection and 13 with rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 28 publications
5
33
1
Order By: Relevance
“…In most cases, the drugs detected were consistent with ART regimens recommended at the time of the study. Many of the men for whom drugs were detected did not demonstrate viral suppression and many were using unusual combinations of drugs, which likely contributed to the high frequency of drug resistance observed in that cohort (19). Unusual patterns of ARV drug use were also detected among seroconverters in the HPTN 061 cohort (19).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In most cases, the drugs detected were consistent with ART regimens recommended at the time of the study. Many of the men for whom drugs were detected did not demonstrate viral suppression and many were using unusual combinations of drugs, which likely contributed to the high frequency of drug resistance observed in that cohort (19). Unusual patterns of ARV drug use were also detected among seroconverters in the HPTN 061 cohort (19).…”
Section: Discussionmentioning
confidence: 82%
“…Many of the men for whom drugs were detected did not demonstrate viral suppression and many were using unusual combinations of drugs, which likely contributed to the high frequency of drug resistance observed in that cohort (19). Unusual patterns of ARV drug use were also detected among seroconverters in the HPTN 061 cohort (19). In another study (HPTN 064 [2009 to 2010]), we found unusual patterns of ARV drug use among HIV-uninfected women in the United States who were at increased risk of HIV acquisition (20,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations